Energy efficiency in cognitive radio assisted D2D communication networks - Ahmad, Mushtaq; Orakzai, Farooq Alam; Ahmed, Ashfaq; Naeem, Muhammad; Iqbal, Muhammad; Umer, Tariq (Telecommunication systems, 2019)
The next generation networks intend to have features like device to device (D2D) connectivity, energy efficiency and spectral efficiency. This paper presents problem formulation for maximization of energy efficiency of cognitive radio assisted D2D networks subject to compliance of transmit powers of cellular users and interference constraints of primary users of broadcast network. Cognitive radio network (CRN) users are cellular users comprising of cellular and D2D users. Cellular users can opt any of the cellular or D2D mode. These CRN users opportunistically utilize spectrum of television (TV) white spaces. The problem thus formulated is NP-complete. Mesh adaptive direct search (MADS) algorithm has been used to find ε -optimal solution. The results of MADS are compared with the global optimal solution obtained by exhaustive search algorithm (ESA). The simulation results reveal that MADS’ performance is equally good as that of ESA in most of the cases. MADS outperforms ESA in terms of energy efficiency comparison. Simulation results compare results of utility value, spectral efficiency and admission of CRN users with two types of utilities, i.e., utility with maximization of energy efficiency and utility without maximization of energy efficiency. Results testify that utility with maximization of energy efficiency outperforms its counterpart utility. MADS is also ideal algorithm as it has low computational complexity as compared to ESA. Computational complexity of ESA increases exponentially as numbers of users increase making MADS obvious choice for real life networks comprising of large number of cellular users.